NR2F2 plays a major role in insulin-induced epithelial-mesenchymal transition in breast cancer cells - Baili Xia; Lijun Hou; Huan Kang; Wenhui Chang; Yi Liu; Yanli Zhang; Yi Ding (BMC Cancer, 2020)
Abstract Background The failure of treatment for breast cancer usually results from distant metastasis in which the epithelial-mesenchymal transition (EMT) plays a critical role. Hyperinsulinemia, the hallmark of Type 2 diabetes mellitus (T2DM), has been regarded as a key risk factor for the progression of breast cancer. Nuclear receptor subfamily 2, group F, member 2 (NR2F2) has been implicated in the development of breast cancer, however its contribution to insulin-induced EMT in breast cancer remains unclear. Methods Overexpression and knockdown of NR2F2 were used in two breast cancer cell lines, MCF-7 and MDA-MB-231 to investigate potential mechanisms by which NR2F2 leads to insulin-mediated EMT. To elucidate the effects of insulin and signaling events following NR2F2 overexpression and knockdown, Cells’ invasion and migration capacity and changes of NR2F2, E-cadherin, N-cadherin and vimentin were investigated by real-time RT-PCR and western blot. Results Insulin stimulation of these cells increased NR2F2 expression levels and promoted cell invasion and migration accompanied by alterations in EMT-related molecular markers. Overexpression of NR2F2 and NR2F2 knockdown demonstrated that NR2F2 expression was positively correlated with cell invasion, migration and the expression of N-cadherin and vimentin. In contrast, NR2F2 had an inverse correlation with E-cadherin expression. In MDA-MB-231, both insulin-induced cell invasion and migration and EMT-related marker alteration were abolished by NR2F2 knockdown. Conclusions These results suggest that NR2F2 plays a critical role in insulin-mediated breast cancer cell invasion, migration through its effect on EMT.